Epstein–Barr virus–host cell interactions: an epigenetic dialog? - Niller, Hans H.; Szenthe, Kalman; Minarovits, Janos (Frontiers in Genetics, 2014)
Epstein-Barr virus (EBV) is associated with diverse lymphoid and epithelial malignancies. Their molecular pathogenesis is accompanied by epigenetic alterations which are distinct for each of them. While lymphoblastoid cell lines (LCLs) derived from B cells transformed by EBV in vitro are characterized by a massive demethylation and euchromatinization of the viral and cellular genomes, the primarily malignant lymphoid tumour Burkitt’s lymphoma (BL) and the epithelial tumours nasopharyngeal carcinoma (NPC) and EBV-associated gastric carcinoma (EBVaGC) are characterized by hypermethylation of a multitude of cellular tumour suppressor gene loci and of the viral genomes. In some cases, the viral latency and oncoproteins including the latent membrane proteins LMP1 and LMP2A and several nuclear antigens (EBNAs) affect the level of cellular DNA methyltansferases or interact with the histone modifying machinery. Specific molecular mechanisms of the epigenetic dialogue between virus and host cell remain to be elucidated.